2022
DOI: 10.3389/fbioe.2022.837295
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Growth Factors Promote hBMSCs Osteogenic Differentiation in a Co-Culture System With HUVECs

Abstract: Osteogenesis is a complex physiologic process that occurs during bone regeneration. This process requires several growth factors that act on bone marrow-derived mesenchymal stem cells (BMSCs). Concentrated growth factor (CGF) is a new-generation platelet-rich derivative that is an appealing autologous material for application in tissue repair and bone regenerative medicine because it contains a variety of fibrin and growth factors. In this study, the effects of CGF on the proliferation and osteogenic different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Currently, ALP , Runx2 , OCN (osteocalcin), and COL-I have been widely recognized as specific markers for osteogenic differentiation. 28,29 The introduction of specific biomolecules can promote bone healing. Boden et al 30 demonstrated in clinical studies that BMP2 has a promoting effect on bone formation in spinal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ALP , Runx2 , OCN (osteocalcin), and COL-I have been widely recognized as specific markers for osteogenic differentiation. 28,29 The introduction of specific biomolecules can promote bone healing. Boden et al 30 demonstrated in clinical studies that BMP2 has a promoting effect on bone formation in spinal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that 10% concentrated growth factor (CGF) had a significant osteogenic effect on human bone marrow mesenchymal stem cells (hBMSCs) directly co-cultured with human umbilical vein endothelial cells (HUVECs). The researchers suggest that autophagy activated by the mTOR/ULK1 pathway and CX43-mediated intercellular communication may play regulatory roles in promoting hBMSCs osteogenic differentiation [29].…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between osteoblasts and osteoclasts can induce osteoporosis [15]. While hBMSCs can be induced into osteoblasts and improved ability of hBMSCs osteogenic differentiation are the key to bone regeneration [16]. Therefore, it is necessary to develop alternative agents effectively to treat osteoporosis in older patients.…”
Section: Discussionmentioning
confidence: 99%